Letter (copy) : Save the Basque Children Fund - Citrine, Walter, 1887-1983
037-0074-001 WMC/FC/EW/178 Secretary's 21st July, 1937. Mr. R. Calderwood, Burgh of Darvel, 69, John Morton Crescent, Darvel. Ayrshire. Dear Mr. Calderwood, "SAVE THE BASQUE CHILDREN" FUND. I was very pleased indeed to receive your letter of the 19th inst., this morning, and to hear of the success of your effort to raise money for the above fund and to collect clothes for the children. This is very encouraging, and I shall be glad if you will kindly convey to all concerned our very best thanks for their help. Funds are urgently needed to maintain the children in the homes that have been found for them, and as it is not known how long the children will be in this country, you will realise how necessary it is for continued assistance. I shall be glad if you will kindly send your cheque to me at the above address. The clothing should be forwarded to the National Committee for the Care of Basque Children at 53, Marsham Street, London, S.W.1. Again thanking you for your interest in this matter. Yours sincerely, General Secretary. 292/946/37/74